Empowering Communities through Sustainable Partnerships: Bash Coffee's Role in Literary Partnership Initiatives - Maspul, Kurniawan Arif (Indonesian Journal of Social Development, 2024)
This qualitative study explores the transformative potential of coffee roasteries' sustainable collaborations and community involvement activities in Al Qassim, Saudi Arabia, with a particular focus on Bash Coffee's literary partnership initiatives. The study examines how these programs affect community involvement, educational growth, cultural appreciation, and social well-being. The study reveals the consequences and narratives related to these actions using qualitative study approaches, including interviews with stakeholders. The findings highlight the need for long-term relationships for community empowerment and social sustainability. The study relates to the larger scientific conversation about the value of literature in societal development by providing insights into the transforming impact of literature in the formation of a vibrant literary society. The findings enable establish and sustain literary acquaintances, while also showing the intriguing possibility of coffee roasteries as major stakeholders in boosting community resilience and well-being.